Beneficial and Detrimental Remodeling of Glial Connexin and Pannexin Functions in Rodent Models of Nervous System Diseases - Brocardo, Lucila; Acosta, Luis Ernesto; Piantanida, Ana Paula; Rela, Lorena (Frontiers in Cellular Neuroscience, 2019)
A variety of glial cell functions are supported by connexin and pannexin proteins. These functions include the modulation of synaptic gain, the control of excitability through regulation of the ion and neurotransmitter composition of the extracellular milieu and the promotion of neuronal survival. Connexins and pannexins support these functions through diverse molecular mechanisms, including channel and non-channel functions. The former comprise the formation of gap junction-mediated networks supported by connexin intercellular channels and the formation of pore-like membrane structures or hemichannels formed by both connexins and pannexins. Non-channel functions involve adhesion properties and the participation in signaling intracellular cascades. Pathological conditions of the nervous system such as ischemia, neurodegeneration, pathogen infection, trauma and tumors are characterized by distinctive remodeling of connexin expression and function. However, whether these changes can be interpreted as part of the pathogenesis, or as beneficial compensatory effects, remains under debate. Here we review the available evidence addressing this matter with a special emphasis in mouse models with selective manipulation of glial connexin and pannexin proteins in vivo. We postulate that the beneficial vs. detrimental effects of glial connexin remodeling in pathological conditions depend on the impact of remodeling on the different connexin and pannexin channel and non-channel functions, on the characteristics of the inflammatory environment and on the type of interaction among glial cells types.